Quantitative autofluorescence findings in patients undergoing hydroxychloroquine treatment. (14th May 2022) - Parrulli, Salvatore; Cozzi, Mariano; Airaldi, Matteo; Romano, Francesco; Viola, Francesco; Sarzi‐Puttini, Piercarlo; Staurenghi, Giovanni; Invernizzi, Alessandro
Abstract: Background: To measure quantitative autofluorescence (qAF) in patients under treatment with hydroxychloroquine (HCQ) and at risk of retinal toxicity but with no apparent signs of retinal toxicity and to compare it with that of untreated subjects. Methods: Consecutive patients at risk for the development of HCQ retinal toxicity (duration of treatment >5 years or daily HCQ dose >5 mg/kg of actual body weight [ABW]) but no alterations on spectral domain—optical coherence tomography, short‐wavelength autofluorescence and 10–2 visual field examination were recruited. Healthy subjects matched by age and sex were also enrolled in the study. All subjects underwent qAF measurements in one eye. Images were analysed using the conventional qAF grid by Delori calculating the qAF of eight sectors of the intermediate ring and the mean of those values (qAF8 ). Results: Thirty‐nine patients treated with HCQ (38 females, mean age 52.1 ± 8.6 years) and 39 untreated subjects (38 females, mean age 51.2 ± 8.6 years) were included. In both HCQ patients and untreated subjects, qAF8 was positively correlated with age ( p  = 0.004). Although HCQ patients showed a higher mean qAF8 compared with untreated subjects (294.7 ± 65.3 vs. 268.9 ± 57.5), the difference was not significant ( p  = 0.068). HCQ patients showed significantly higher mean qAF values in the inferior‐temporal, inferior and inferior‐nasal sectors of the intermediate ring of qAF grid compared with untreated subjects (all p  < 0.05). Conclusions: These results suggest a possible preclinical increase of qAF values in inferior parafoveal sectors probably induced by HCQ exposure.